Starting a Swedish national quality registry for orthognathic surgery: a tool for auditing fundamentals of care - Mats Sjöström; Bodil Lund; Bo Sunzel; Martin Bengtsson; Mikael Magnusson; Lars Rasmusson (BMC, 2022)
Abstract Background National quality registries (NQRs) provide open data for user-directed acquisition. National Quality Registry (NQR) data are often used to analyze the rates of treatment success and adverse events for studies that aim to improve treatment quality and patient satisfaction. Thus, NQRs promote the goal of achieving evidence-based therapies. However, the scientific literature seldom focuses on the complex process of initiating, designing, and implementing an NQR. Starting an NQR may be particularly challenging in a setting where specialized care is decentralized, such as orthognathic surgery in Sweden. The present study describes the initiation and early phases of a new NQR for orthognathic surgery in Sweden. Methods The initial inventory phase included gaining knowledge on regulations, creating economic plans, and identifying pitfalls in existing NQRs. Next, a crude framework for the registry was achieved. Outcome measures were selected with a nation-wide questionnaire, followed by a Delphi-like process for selecting parameters to include in the NQR. Our inclusive process comprised a stepwise introduction, feedback-based modifications, and preparatory educational efforts. Descriptive data were collected, based on the first 2 years (2018-2019) of registry operation. Results Two years after implementation, 862 patients that underwent 1320 procedures were registered. This number corresponded to a 91% coverage rate. Bimaxillary treatments predominated, and the most common were a Le Fort I osteotomy combined with a bilateral sagittal split osteotomy (n = 275). Reoperations were conducted in 32 patients (3.6%), and the rate of patient satisfaction was 95%. Conclusions A National Quality Registry should preferentially be started and maintained by an appointed task force of active clinicians. A collaborative, transparent, inclusive process may be an important factor for achieving credibility and high coverage, particularly in a decentralized setting.